Creep of Untreated donax grandis polymer composites - Bajuri, E.N (University Malaysia Sarawak, (UNIMAS), 2006)
Donax Grandis fibre reinforced unsaturated polyster composites with 10% and 20% of volume fraction had been prepared. The composites were used to conduct an experimental study in order to investigate the creep behaviour of untreated Donax Grandis fibre polymer composites. This experiment had been conducted in compression mode under room temperature 23 degree Celsius at various loads for each of volume fraction.